(untitled) (Global Journal of Science Frontier Research, 2020)
The article discusses experimental discoveries recently made at the Large Hadron Collider (LHC) and not received an explanation in the Standard Model. The recognition of the polarization of quantum vacuum (dark matter) under the action of ultra relativistic protons and superpower magnetic and electric fields distorts the spatial patterns in the LHC and allows us to state the presence of the third channel of proton interaction in the LHC, in addition to their mutual collisions.